1998
DOI: 10.1002/(sici)1097-0142(19980815)83:4<732::aid-cncr15>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Malignant lymphoma involving the prostate

Abstract: BACKGROUND Malignant lymphoma involving the prostate is rare, and to the authors' knowledge the factors determining patient outcome have not been studied in a large series. METHODS The authors evaluated the clinical and pathologic findings in 60 cases of non‐Hodgkin's lymphoma and 2 cases of Hodgkin's lymphoma involving the prostate. A variety of clinical and histologic findings were considered as factors predictive of patient outcome. RESULTS Lymphoma tended to occur in elderly men, with a mean age at diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
149
2
11

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(170 citation statements)
references
References 25 publications
8
149
2
11
Order By: Relevance
“…Th e largest case series comprising the pathology database of fi ve university hospitals spanning an aggregate of 200 years has documented only 62 cases of lymphoma of the prostate (1). A further review of 5962 autopsy specimens revealed that only 49 (0.82%) of the patients had non-Hodgkin's lymphoma of the prostate (3).…”
Section: Discussionmentioning
confidence: 99%
“…Th e largest case series comprising the pathology database of fi ve university hospitals spanning an aggregate of 200 years has documented only 62 cases of lymphoma of the prostate (1). A further review of 5962 autopsy specimens revealed that only 49 (0.82%) of the patients had non-Hodgkin's lymphoma of the prostate (3).…”
Section: Discussionmentioning
confidence: 99%
“…In accordance with the findings of other studies, nearly all cases of the genitourinary hematolymphoid neoplasms were B-cell non-Hodgkin's lymphomas. [3][4][5][6][7] Most cases in our series involved the kidney and testis; somewhat surprisingly, there were more lymphomas identified within the prostate than in the bladder. This most likely reflects the increased relative frequency of prostate biopsies rather than any increased propensity for lymphomagenesis.…”
Section: Discussionmentioning
confidence: 99%
“…The recognition of the presence of occasional rudimentary lymphoid nodules, cases of extramedullary hematopoiesis within the prostate, and documented cases of lymphoma limited to the prostate without pelvic or retroperitoneal lymph node involvement have shown that primary prostatic lymphomas exist. 5 Most primary lymphomas of the prostate are non-Hodgkin's lymphomas and are predominantly of B-cell lineage. In our series, DLBCL was the most common subtype, followed by SLL/CLL and follicular lymphoma, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] A group of B-cell lymphomas composed of small lymphocytes are characterized by relatively indolent clinical course. [4][5][6][7] These biologically indolent B-cell lymphomas includes the following five categories: small lymphocytic lymphoma/CLL (SLL/CLL), lympho-plasmacytic lymphoma (LPL), marginal zone B-cell lymphoma (MZBL) (aka MALT lymphoma), follicular lymphoma (FL), and mantle cell lymphoma (MCL).…”
Section: Introductionmentioning
confidence: 99%